Spinal Primitive Neuroectodermal Tumor Resembling a Primary Vertebral Tumor - Ganiüsmen, Ozan; Çıtak, Güven; Korkmaz, Hakan; Samancıoğlu, Ali; Demirçivi Özer, Füsün (Journal of Nervous System Surgery, 2014)
Primitive neuroectodermal tumors are the most common malignant tumors of the childhood and early childhood. Primary spinal primitive neuroectodermal tumor (PNET) are rare. In recent years the number of patients have entertained increased awareness of PNET, and more than 80 cases have been reported. At every level of the spinal region, and in each compartment spinal PNET may be seen, Although its intramedullary, intradural-extramedullary, and extradural components can be easily excised, and combination treatment can be applied, the longest survival period hardly approaches six years. A case of a spinal PNET resembling to a primary tumour in a 17 -year- old patient who applied with a L1 fracture was presented. According to our knowledge, corpus-based PNET has not been previously submitted. The patient underwent surgery (including posterolateral stabilization because of the presence of a fracture), radiotherapy and chemotherapy in that order and he was followed up for 2.5 years.